Geography, Trade Patterns, and Economic Policy - Asilis, Carlos (IMF Working Papers; Working Paper ;, 1994)
This paper presents a geographical theory of location and interregional trade. Location is treated as an endogenous variable by firms, consumers and perfectly mobile workers in a two-sector economy. Space plays a central role owing to transportation costs, market access, and distance from polluting industrial centers. The model is used to examine: (1) aspects of a compensating-differential theory of regional unevenness, (2) the theoretical formulation of a gravity theory of trade patterns, (3) the geographic basis for industrial and environmental policy, and (4) the interaction between reductions in transportation costs, location patterns, and technological improvements.